2022
DOI: 10.3389/fmed.2022.761655
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized, Double Blind, Placebo Controlled, Clinical Trial to Study Ashwagandha Administration in Participants Vaccinated Against COVID-19 on Safety, Immunogenicity, and Protection With COVID-19 Vaccine–A Study Protocol

Abstract: IntroductionVaccines have emerged as the most effective tool in the fight against COVID-19. Governments all over the world have rolled out the COVID-19 vaccine program for their populations. Oxford-AstraZeneca COVID-19 vaccine (COVISHIELD™) is widely used in India. A large number of Indian people have been consuming various traditional medicines in the hope of better protection against COVID-19 infection. Several studies have reported immunological benefits of Withania somnifera (Ashwagandha) and its potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Indeed, it is possible that these two together might compete with each other and exhibit moderate inhibition of CYP2C8 activity. Interestingly, there was no mention of any significant interaction or adverse reaction during the clinical studies conducted with ashwagandha and AYUSH-64 ( Gundeti et al, 2020a ; Reddy et al, 2020 ; Chopra et al, 2021 ; Chopra et al, 2022 ; Singh et al, 2022 ). The HDIs and pharmacokinetic parameters presented in the current study provide insights into having safer therapeutic options for mitigating SARS-CoV-2 as well as their use for the treatment of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that these two together might compete with each other and exhibit moderate inhibition of CYP2C8 activity. Interestingly, there was no mention of any significant interaction or adverse reaction during the clinical studies conducted with ashwagandha and AYUSH-64 ( Gundeti et al, 2020a ; Reddy et al, 2020 ; Chopra et al, 2021 ; Chopra et al, 2022 ; Singh et al, 2022 ). The HDIs and pharmacokinetic parameters presented in the current study provide insights into having safer therapeutic options for mitigating SARS-CoV-2 as well as their use for the treatment of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The organ-preserving results of Withania somnifera are used to reduce systemic inflammation, which protects against the severity of inflammation-induced organ damage. In addition to these antiviral actions, Bethany has a confirmed sedative role in supporting mental health, which may be very useful in the control and treatment of COVID-19 [80]. Since the interaction of SARS-CoV-2 S-protein RBD and ACE2 receptor is very important for viral entry into host cells during infection, thus bioactive compounds of Withania somnifera such as withanone and withaferin A may be involved in the management and treatment of COVID-19 [81].…”
Section: Methodsmentioning
confidence: 99%
“…However, there were some adverse reactions reported in people due to prior allergies ( Sumito et al., 2021 ). Although Withania somnifera cannot fully eradicate SARS-CoV-2, studies have shown that co-administration of Ashwagandha with the COVISHIELD™ vaccine enhanced the antibody titers, particularly after the first dose of the vaccine ( Chopra et al., 2022 ).…”
Section: Strategies For the Treatment Of Sars-cov-2mentioning
confidence: 99%